O nekaterih iracionalnih desetiških zapisih - Jamnik, Gaja (Matrika, 2022)
In the paper it is discussed how to determine irrationality of a real number based on the properties of the sequence of its decimal expansions. Morover, a number that has sequence of prime numbers for its decimals is examined in more detail.
Keywords: decimal numbers; decimalna števila; iracionalna števila; irrational numbers; number theory; teorija števil